Variety, technological intensity, and economic growth at the regional level in Argentina - Florencia Barletta; Diana Suárez (PSL Quarterly Review, 2024)
The objective of this paper is to study the relationship between productive structure and economic performance at the subnational level in Argentina. Based on a dataset at the subnational level, we study the impact on economic growth of three types of productive patterns: i) productive efficiency (W), ii) related variety (RV), and iii) unrelated variety (UV). In addition, we explore to what extent this impact is conditioned by the level of technological intensity of productive structures. Results show that unrelated variety positively impacts on economic growth when it happens within a context of high levels of technological intensity of productive structures. When this is not the case, the impact might even be negative, or there may be no impact at all.
Keywords: R11; O18; O30; 330; variety; technological intensity; growth; Argentina